ASPEK PENGETAHUAN SIKAP DAN PERILAKU MASYARAKAT KAITANNYA DENGAN PENYAKIT TB PARU - Manalu, Helper Sahat P; Sukana, Bambang (Badan Penelitian dan Pengembangan Kesehatan, 2011)
Tuberculosis in Indonesia still ranted third largest in the world after India and China with approx 539,000 new cases and the number of deaths around 101.000/year. Knowledge factors of pulmonary is a very important factor in the transmission of Tuberculosis. To know the aspects of knowledge, attitude and behavior of people in connection with pulmonary TB disease has been studied in Tangerang Regency. The purpose of this study is to solve the problem of knowledge/community behavior related to transmission of pulmonary TB. This study uses cross sectional design which aims to determine the knowledge attitude and behavior of the public about tuberculosis, and the factors that influence the implementation of the tuberculosis program. Sampling was done by purposive against the family. Results in-depth interviews and focus group discussions stated that their knowledge and their behavior is not good enough, people's attitudes towards people with already good. Extension of pulmonary TB has not performed optimally. Low level of public knowledge about tuberculosis, health workers are expected to continue to do more intensive counseling.